CONSUMPTION OF FUNCTIONAL FOOD AND KNOWLEDGE OF ITS A TTRIBUTES: A QUANTITATIVE STUDY OF CONSUMERS IN PUNJAB PROVINCE, PAKISTAN - M. U. Zafar; Q. Ping; S. Khan; M. U. Zafar; R. Rauf (Journal of Animal and Plant Sciences, 2022)
The different scientific studies have identified the beneficial physiological role and effects of functional foods (FFs). No doubt the knowledge of nutrition is primarily important in addressing human physical and physiological health along with human wellness. The study is planned to explore the consumers’ knowledge about the different attributes of FFs and their consumption pattern. A purposive multistage random sampling design was used for the selection of 400 consumers of FFs from four major cities of Pakistan. The shopping centers and consumers were randomly selected. The analysis demonstrates that about more than 30 percent of the consumers had knowledge to a great extent of perceived quality, appearance package, organoleptic, functionality, price and brand attributes and about 40 percent of the consumers had knowledge to some extent of these attributes. Analysis reflects that from 33 to 86 percent of consumers were using often modified cereals, oats, bread, canola oil, orange juice, grape juice, modified yogurt, milk fortified with vitamins, green tea, energy drinks, ginger, and turmeric. It is suggested that creating awareness and building confidence about FFs among consumers will be useful for promotion of FFs in Pakistan. As the elder family members are more concerned about their health, they should motivate their children to adopt good food habits which are imperative to improve their quality of life. The FFs providers and manufactures should equip their R&D department with the latest development in functional foods sector through coordinating food scientists, university food experts and industrialists for manufacturing the specific food products which are beneficial for human health.
Keywords: Functional Food (FF); Product Attributes; Consumptions; Reasoned Action Theory